2013
DOI: 10.1155/2013/253985
|View full text |Cite
|
Sign up to set email alerts
|

Energy Conditions in a Generalized Second-Order Scalar-Tensor Gravity

Abstract: The study of energy conditions has many significant applications in general relativistic and cosmological contexts. This paper explores the energy conditions in the framework of the most general scalartensor theory with field equations involving second-order derivatives. For this purpose, we use flat FRW universe model with perfect fluid matter contents. By taking power law ansatz for scalar field, we discuss the strong, weak, null and dominant energy conditions in terms of deceleration, jerk and snap paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Some other well-known examples include Brans-Dicke gravity, generalized scalar-tensor theory, f (τ ) gravity, where τ is a torsion, Gauss-Bonnet gravity and its generalized forms like f (G) gravity, f (R, G) gravity, and f (τ, τ G ) theory, etc. [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Some other well-known examples include Brans-Dicke gravity, generalized scalar-tensor theory, f (τ ) gravity, where τ is a torsion, Gauss-Bonnet gravity and its generalized forms like f (G) gravity, f (R, G) gravity, and f (τ, τ G ) theory, etc. [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Banijamali et al [26] investigated the energy conditions for non-minimally coupling f (G) theory with L m and found that the WEC is satisfied for specific viable f (G) models. Sharif and Waheed [27] explored the energy bounds in the context of generalized second order scalartensor gravity with the help of a power-law ansatz for the scalar field. Sharif and Zubair [28] derived these conditions in f (R, T, R αβ T αβ ) theory of gravity for two specific models and also examined the Dolgov-Kowasaki instability for particular models of f (R, T ) gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Further the energy conditions of a very generalized second-order scalar-tensor gravity have been discussed by Sharif and Saira [37]. Sharif and Zubair have examined these conditions for f (R, T ) gravity [25] and for f (R, T, R μν T μν ) gravity [38], which involves the nonminimal coupling between the Ricci tensor and the energy-momentum tensor.…”
Section: Introductionmentioning
confidence: 99%